Anakinra and hepatotoxicity in pediatric rheumatology: a case series - Frederico Rajão Martins; André Costa Azevedo; Sara Ganhão; Francisca Aguiar; Mariana Rodrigues; Iva Brito (BMC, 2023)
Abstract Background Anakinra is a recombinant interleukin-1 (IL-1) receptor antagonist used in systemic juvenile idiopathic arthritis (sJIA), refractory Kawasaki disease (KD) and cryopyrin-associated autoinflammatory syndrome (CAPS). Anakinra associated hepatotoxicity, while rare, has been described in several cases in daily practice. ​In this case series the authors describe three pediatric patients with this side effect in the setting of severe macrophage activation syndrome (MAS) in KD and sJIA. Case presentation The first patient was a 12-year-old boy who presented with fever, maculo-papular exanthema and polyarthralgia. Tonsillitis, distal limb induration and tender cervical lymph nodes were observed. Erythrocyte-sedimentation rate (ESR), C-reactive protein (CRP), ferritin (11,975 ng/mL), D-dimers (5,98 mg/L FEU) and soluble CD25 (3645 pg/mL) levels were elevated. Exclusion of sepsis / toxic shock syndrome warranted introduction of IV methylprednisolone and immunoglobulin (IG IV), with partial response. A MAS secondary to KD was assumed, and anakinra 2 mg/kg/day was introduced. Twenty days later he developed new-onset nausea and severe cyto-cholestasis, normalizing after 2 months of drug discontinuation. Posterior onset of polyarthritis and evanescent lead to a final diagnosis of sJIA. The second patient was a 2-year-old boy with a 10-day history of fevers, generalized rash, hepatosplenomegaly and strawberry tongue. Leucocytosis with neutrophilia and elevated CRP were observed. Initial treatment with IVIG in the setting of incomplete KD was ineffective. Mild anaemia, leukopenia and very high serum ferritin (maximum 26,128 ng/mL) ensued. Presumptive sJIA associated MAS was treated with IV methylprednisolone and anakinra 2 mg/kg/day, with prompt response. Four weeks later transaminitis was detected, and temporary anakinra suspension led to normalisation of laboratorial values. The third case related to a 4-year-old boy presenting with fever, maculopapular rash and cervical lymphadenopathy. CRP and ESR were elevated, and KD was diagnosed. IVIG and methylprednisolone were initiated with clinical worsening, warranting for anakinra introduction at 2 mg/kg/day. After three weeks, liver enzymes progressively elevated, resolving on 2 weeks of anakinra discontinuation. Conclusions To the best of our knowledge, this is the first case series describing anakinra associated hepatotoxicity in pediatric patients with rheumatic diseases other than sJIA, bringing additional insight to therapeutic monitoring in patients undergoing this treatment.